Performance of voice over frame relay - Khan, T.; Rashid, M.A. (Massey University, 2004)
Frame Relay (FR) represents one of the most important paradigm shifts in modern telecommunication. This technology is beginning to evolve from data only application to broad spectrum of multimedia users and potential to provide end users with cost effective transport of voice traffic for intra office communication. In this project the recent development in voice communication over Frame relay is investigated. Computer ssimulations were carried out using the powerful simulation software OPNET. Performance measures such as delays, jitter, and throughput are reported. It is evident from the results that real-time voice or video across a frame relay network providing acceptable performance is possible.
Keywords: Frame relay; Voice communication; Telecommunication